'A Matter of Doubt and Uncertainty': John Gladstone and the Post-Slavery Framework of Labour in the British Empire. Issue 1 (2nd January 2022) - Hossain, Purba
ABSTRACT: The abolition of slavery in the British Empire in 1833 marked an important juncture in imperial and labour history. It led to the beginning of the government-sanctioned system of Indian indentured migration to British plantation colonies, and it fostered the circulation of ideas, arguments and debates about acceptable forms of labour. This essay focuses on the role and activities of British merchant-planter John Gladstone to investigate the trans-imperial nature of the indenture debates and the post-slavery framework of labour. It explores his personal and professional networks, his role in establishing and popularising the indenture trade, and his ideas of free labour to demonstrate that Gladstone's intervention had two major effects. His activities ensured that Indian indenture became the primary legal labour movement that followed slave labour in destination colonies, and created a pre-emptive system for discussing indenture in terms of the twin rubrics of 'free' and 'unfree'.